Examination of Internet Usage Status and Affecting Factors in Primary School Students - Merve Kolcu; Selda Çelik; Rabiye Güney; Merdiye Şendir (Çocuk Dergisi)
Objective: The aim of this study was to examine the internet usage status of primary school students and the affecting factors. Materials and Methods: The population of this descriptive study included a total of 480 students studying in a primary school, and the sample consisted of 455 students. The data were collected using a data collection form created by the researchers. In the analysis of the obtained data, frequency, mean, chi-square test and logistic regression analysis were used. Results: Of the sample primary school students, 27% had a computer, 17.1% had a smart phone, 82% had an internet connection at home, 66.6% spent 1-2 hours on the internet every day, and 60% did not have any restrictions on internet use imposed on them by their families. A significant relationship was found between the students’ daily internet usage time and their grades (p˂0.05). Conclusion: As a result of this study, it was concluded that daily internet usage time was affected by the age of the children, having their own computer, having their own mobile phone, existence of internet connection at home and imposition of internet limitation by the family. It is recommended to conduct studies with larger samples, since interventions for behavior change in childhood are more effective.